Spiral Nematode Helicotylenchus spp. (Nematoda: Tylenchida: Hoplolaimidae) - William T. Crow (EDIS)
Also  published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/NEMATODE/spiral_nematode.htm